The role of non-governmental organization in the developing and implementation of dementia policy - Oleksandra Khudoba (Theory and Practice of Public Administration, 2019)
Non-governmental organizations are gradually, but increasingly, engaged in global governance through activities that once were or are characteristic of government structures. In fact, NGOs gradually fill the niche that is left out of government attention at the subnational or national levels and globally, especially in solving dementia issues. We could not find any Ukrainian scientific developments in the context of the national dementia policy formation or strategic decision-making management in this case, as well as the disclosure of the role of key partners regarding dementia. Since NGOs attract a great attention as one of the very important agents in the management process, the purpose of this article is to analyze the mechanisms of NGOs’ and governmental structures’ cooperation in the context of medical and social services development as well as the presentation of new initiatives to combat dementia. Involving civil society organizations can have a significant impact on two different but interlinked activities: 1) Strengthening democratic processes through the impact of policy formation and advocacy: 2) promoting the empowerment of recipients of medical and social assistance, especially those with limited financial resources. Research on health development in general, as well as counteraction dementia in particular, is essential for the development of any country. NGOs, which are considered valuable partners, have made and continue to make a significant contribution by supporting relevant and effective studies. The process of solving these problems requires a cross-sectoral approach that includes interdisciplinary teams and comprehensive methodologies. The influence of NGOs on decision-making processes is huge and indisputable, besides international organizations are increasingly involved in these processes. They become very influential participants. Ukraine is one of the biggest country in Europe with ageing population and extremely low level of dementia awareness. The first step in developing dementia policy is to attract attention to dementia as a medical and social problem at the national level involving policy makers into the discussion. In launching this process the role of NGOs is invaluable.